2014
DOI: 10.1016/j.jchf.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Is Heart Rate Important for Patients With Heart Failure in Atrial Fibrillation?

Abstract: In patients with CHF and a reduced LVEF, slower resting ventricular rate is associated with better survival for patients in SR but not for those with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 24 publications
7
68
2
4
Order By: Relevance
“…(5,38) However, ventricular rate appears to be a poor predictor of outcomes for patients with concomitant HFrEF and AF. Lower ventricular rates in AF may even be associated with adverse prognosis (39), but why the relationship between heart rate and prognosis should differ by heart rhythm is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…(5,38) However, ventricular rate appears to be a poor predictor of outcomes for patients with concomitant HFrEF and AF. Lower ventricular rates in AF may even be associated with adverse prognosis (39), but why the relationship between heart rate and prognosis should differ by heart rhythm is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In addition, some studies report a similar prognosis between AF and SR in HFrEF. 5,15 As a nationwide heart failure registry, our study has the advantage of both a large sample size and representative HF population. Furthermore, the large number of variables available for adjustment reduces the likelihood of AF being merely a risk marker and strengthens the hypothesis that AF is a true independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that a slower resting ventricular rate is associated with better survival in HFrEF patients with SR but not in those with AF. 5 In Rate Control Efficacy in Permanent Atrial Fibrillation: a Comparison between Lenient versus Strict Rate Control II (RACE II) trial, lenient rate control (<110 beats per minute) did not yield worse outcomes than strict rate control (<80 beats per minute) overall or in the subgroup of patients with HF, many of whom had preserved EF. 6,7 A subgroup analysis from the Candesartan in Heart failure: Assessment of Reduction in Mortality and Morbidity (CHARM) program showed that resting HR is an important predictor of outcome in patients with stable chronic HF without AF, independent of EF or β-blocker use; however, among patients with AF at baseline, HR had no predictive value.…”
mentioning
confidence: 99%
“…Так как в этот анализ были включены больные, обследован-ные, в том числе, до «эры» β-АБ в лечении ХСН, мож-но сделать вывод, что большая частота синусового ритма при ХСН со сниженной систолической функцией серд-ца достоверно ухудшает прогноз. В недавнем анализе выживаемости пациентов с ХСН и синусовым ритмом, проводившемся в Великобритании, было продемон-стрировано достоверное ухудшение прогноза больных на 10 % до и на 13 % после нормализации терапии, в рас-чете на 10 ударов прироста ЧСС [47]. В Шведском реги-ОБЗОРЫ § стре (90 % больных уже на лечении β-АБ) увеличение ЧСС покоя более 60 уд / мин ступенчато повышало риск смерти: +26 % до 70 уд / мин, +37 % до 80 уд / мин, +52 % до 90 уд / мин, +63 % до 100 уд / мин и в 2,69 раза при ЧСС >100 уд / мин [48].…”
Section: оптимальная чсс у больных с синусовым ритмом и хснunclassified